Social representations of the health care of the Mbyá-Guarani indigenous population by health workers - Mirian Benites Falkenberg; Helena Eri Shimizu; Ximena Pamela Díaz Bermudez
ABSTRACT Objective: to analyze the social representations of health care of the Mbyá-Guarani ethnic group by multidisciplinary teams from the Special Indigenous Health District in the south coast of Rio Grande do Sul state (Distrito Sanitário Especial Indígena Litoral Sul do Rio Grande do Sul), Brazil. Method: a qualitative method based on the theory of social representations was used. Data were collected via semi-structured interviews with 20 health workers and by participant observation. The interviews were analyzed with ALCESTE software, which conducts a lexical content analysis using quantitative techniques for the treatment of textual data. Results: there were disagreements in the health care concepts and practices between traditional medicine and biomedicine; however, some progress has been achieved in the area of intermedicality. The ethnic boundaries established between health workers and indigenous peoples based on their representations of culture and family, together with the lack of infrastructure and organization of health actions, are perceived as factors that hinder health care in an intercultural context. Conclusion: a new basis for the process of indigenous health care needs to be established by understanding the needs identified and by agreement among individuals, groups, and health professionals via intercultural exchange.